Synthesis, characterization and spectroscopic studies of two new schiff-base bithienyl pendant-armed 15-crown-5 molecular probes - Pedras, Bruno (2009)
Nickel(II); Palladium(II); Mercury(II); Sodium(I); ; Crown ether, Schiff base, Luminescence